Further Spitzer’s law for widely orthant dependent random variables - Pingyan Chen; Jingjing Luo; Soo Hak Sung (Journal of Inequalities and Applications, 2021)
Abstract The Spitzer’s law is obtained for the maximum partial sums of widely orthant dependent random variables under more optimal moment conditions.